Arbeitslosigkeit und Alterssicherung: der Einfluss früherer Arbeitslosigkeit auf die Höhe der gesetzlichen Altersrente - Christoph Wunder (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– Reductions in the state old-age pension which result from previous periods of unemployment are estimated on the basis of an econometric model whose starting point is the human capital theory. It is possible to differentiate between two negative effects on pensions. Firstly, as the state old-age pension depends on lifetime earnings there is a compensation for years with no earnings, e.g. periods of unemployment. Nevertheless this compensation leads to reduced pension entitlements compared with continuous employment. Secondly, the depreciations of human capital and the missing professional experience cause a deterioration of earnings after re-entry to employment. Empirical findings show that the losses are larger than has so far been assumed in example calculations and are particularly severe for relatively short employment biographies.
Keywords: 330; Alterssicherung; Arbeitslosigkeit - Auswirkungen; Humankapitalansatz; Lohnhöhe; Berufsverlauf; Rentenhöhe